A study of customer satisfaction on Mazda at Cycle & Carriage Bintang Berhad / Shahrul Akmal Kamaruddin - Kamaruddin, Shahrul Akmal (1997)
The objective of this project paper was to identify the level of customer satisfaction on Mazda model in automobile company. The study approach was a research study of Mazda of Cycle & Carriage Bintang Berhad (CCB). Information on the level of satisfaction among the existing customers that sends their car for services at Mazda Service Centre. Cycle & Carriage Bintang Berhad currently embarks on a customer service improvement especially on service after sales and product performance. Thus, Cycle & Carriage Bintang Berhad were set up an action plan on improvement of product, the performance of dealers, upgrade skill and product knowledge to service personnel, and to improve the price premium. However, in the process of delivering an excellent service, Mazda division faces a lot of problem and issues to fulfil customer satisfaction. The study findings show that the current of customer satisfaction is positive but not encouraging enough as the main as expectation and perceived performance. It is due to not support the promise, not deliver things on the right time, and improper management on customer service.